Penyuluhan Hukum kesehatan tentang Tanggung Jawab Etik dan Legal Perawat kepada Mahasiswa Keperawatan: Pengabdian - La Ode Muhammad Karim; Rizki Mustika Suhartono; Amrun Kahar; Mashendra; La Gurusi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Health law counseling is a preventive effort to equip nursing students with a strong understanding of ethical and legal responsibilities in nursing practice. This activity was conducted through an educational and interactive approach based on health law counseling. This community applied a descriptive qualitative method involving 30 nursing students as participants selected purposively. Data were collected through observation, in-depth interviews, and written reflections. The results of the activity showed a significant increase in students' understanding of legal issues such as malpractice, informed consent, and the scope of professional authority. Students also demonstrated increased confidence in responding to legal dilemmas during clinical practice. Law counseling based on case studies and simulation proved effective in building students’ legal awareness and professionalism. The result of this community service affirms the importance of integrating health law into the nursing education curriculum and highlights the need for continuous legal education programs as part of the strategy to improve the ethical and legal competencies of future nurses.